Rehearsal and performance volume in professional ballet: A five-season cohort study - Shaw, J. W.; Mattiussi, A. M.; Brown, D. D.; Williams, S.; Springham, M.; Pedlar, C. R.; Tallent, J. (Journal of Dance Medicine & Science, 2023)
Key Points